MOTIVASI BELAJAR DAN KUALITAS PELAYANAN DOSEN, PENGARUHNYA PADA LITERASI KEUANGAN MAHASISWA AKUNTANSI UNIVERSITAS PATTIMURA: LEARNING MOTIVATION AND QUALITY OF LECTURER SERVICE, ITS INFLUENCE ON FINANCIAL LITERACY OF PATTIMURA UNIVERSITY ACCOUNTING STUDENTS - Putuhena, Hempry; Fauzan, M. Rifkhi; Zalni, Zalni (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
Financial literacy focuses on understanding and implementing financial concepts it in real life. This study aims to examine the influence of learning motivation and service quality of lecturers on student financial literacy. These two variables are very rarely investigated by previous studies. To answer these questions quantitative research methods using the SPSS application. Questionnaires used to be processed with SPSS to answer research questions from as many as 192 respondents. 192 respondents were Pattimura University accounting students who were studying in the even semester of 2022/2023 and were willing to voluntarily become respondents. The results show that motivation affects literacy while the financial quality of lecturer services does not affect financial literacy. Thus, the lecturer always fosters a spirit of student motivation in the activities of each lecture so that students continue to increase their understanding of financial literacy